2011
DOI: 10.1103/physrevb.84.174435
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of the long-range and short-range magnetic order components in SrEr2O4

Abstract: Single-crystal neutron diffraction reveals two distinct components to the magnetic ordering in geometrically frustrated SrEr 2 O 4 . One component is a long-range ordered k = 0 structure which appears below T N = 0.75 K. Another component is a short-range incommensurate structure which manifests itself by the presence of a strong diffuse scattering signal. On cooling from higher temperatures down to 0.06 K, the partially ordered component does not undergo a pronounced phase transition. The magnetic moments in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 18 publications
7
68
0
Order By: Relevance
“…However, there are several aspects of the magnetism not explained by the original theories. For example, SrEr 2 O 4 exhibits long-range Néel order [17], characteristic of a small J 2 , coexisting with diffuse magnetic scattering [18]. Monte Carlo simulations reveal that the pattern from the latter is best described by dominant J 2 AFM exchange interactions, and this finding is consistent with quasi-1D UUDD ordering.…”
Section: Introductionsupporting
confidence: 72%
“…However, there are several aspects of the magnetism not explained by the original theories. For example, SrEr 2 O 4 exhibits long-range Néel order [17], characteristic of a small J 2 , coexisting with diffuse magnetic scattering [18]. Monte Carlo simulations reveal that the pattern from the latter is best described by dominant J 2 AFM exchange interactions, and this finding is consistent with quasi-1D UUDD ordering.…”
Section: Introductionsupporting
confidence: 72%
“…This result could be compared with previous observations, e.g., the SrEr 2 O 4 or SrHo 2 O 4 compounds [8][9][10] where it was shown that only one out of the two Er or Ho sites possesses a sizable magnetic moment (the PND data are insufficient to determine which of the two sites has the higher magnetic moment). However, the comparison is not straightforward, as we are comparing the in-field behavior of SrDy 2 O 4 with zero-field properties of SrEr 2 O 4 and SrHo 2 O 4 .…”
Section: B Pnd In An Applied Magnetic Fieldmentioning
confidence: 56%
“…In SrEr 2 O 4 , a k = 0 long-range antiferromagnetic order with magnetic moments parallel to the c axis on one Er site and a quasi-one-dimensional (1D) short-range antiferromagnetic order with the moments along the a axis on another Er site are found to coexist down to the lowest temperatures [8,9]. In SrHo 2 O 4 , the magnetic structure is similar to that of SrEr 2 O 4 , but the k = 0 component has only a limited correlation range and the magnetic moments in the quasi-1D structure point along the b axis [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…It was not possible to determine which particular site contributed to the ordering, as the magnetic moments may be swapped between the two sites without changing the calculated PND pattern significantly 17 . The situation with the low-temperature magnetic structure of SrEr 2 O 4 became much clearer after the publication of single crystal polarised neutron diffraction results 18 , which are summarised in Fig. 4.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 4c, for example, clearly shows the two rods are at positions (0, k, 1/2 + δ) and (0, k, 3/2 − δ), where δ is dependent upon k. A Monte Carlo simulation 18 showed that a simple model based on a ladder of triangles in which the nearest-neighbour interactions are approximately five times stronger than the next-nearest-neighbour interactions satisfactorily mimics the observed diffuse scattering patterns.…”
Section: Introductionmentioning
confidence: 99%